Analysis and Design of Modern Style Kebaya Store Sales System Using PIECES and OOAD Methods - Anitya Jauza Rachmad; Edy Rahman Syahputra; Halim Maulana (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2022)
Toko Kebaya Style Modern is a business engaged in the sale of kebaya clothes, which is located in at Jalan Besar Delitua Kab. Deli Serdang. Promotion system and a conventional data collection and manually create outreach than the market share gained by Toko Kebaya Style Modern. Therefore, they invented a way of marketing and sales through the Internet or ECommrece which aims to provide convenience to the seller and the buyer in the process of buying and selling and collection of products and customers. The method used in this research is the method of object-oriented approach Object methods Orientd Analysis Program (OOAD) as well as visual modeling that helps to capture the structure and behavior of objects. This visual modeling using the Unified Modeling Language (UML) and feasibility analysis menggunakann PIECES (Performance, Information, Economic, Control, Eficiensi, and Service). E-commerce system can help Toko Kebaya Style Modern in the sales process, data collection and management products that are online as well as disseminating information about the product rapidly and expand the coverage area of marketing and improving the quality of services better to their customers so as to strengthen the relationship between the company and customers, and ultimately bring benefits to the company in the market and meet customers' needs for information is up to date